DIGITAL IMAGE COMPRESSION USING INTEGER BASEDTRANSFORM ALGORITHM - Sulttan, Bushra A (Al-Nahrain Journal of Science, 2018)
One of the most problems in computer application is the storage and transmission of images that makes the field of developing the image compression. For that, various compression methods have been proposed using different techniques to achieve high compression ratios and high image quality. One of the image compression methods is transformed based image compression using integer wavelet transform (IWT), which is the main purpose of this paper. This paper describes an algorithm of compression and decompression using (IWT). In IWT, we perform all possible decomposition of an image (i.e. until image size 2×2), after that the resultant coefficients are arranged according to their impotency using zigzag arrangement and divided on factor related to their impotency (increase the factor with low impotency), to make low impotency coefficient related to zero. Remap the values to the range (1.255) (i.e. byte). Then perform lossy or lossless Run Length Coding (RLC) to construct the codebook of the compressed image. The effects of different RLC and different initial quantization factor, image contents and compression ratios assessed. The results provide a good reference for application developers to choose a good wavelet compression system for their application